SUFFIXES USE IN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL ON TENTH GRADE STUDENT’S: A MORPHOLOGY PERSPECTIVE - Suwantica Kusumandari (Jurnal Akrab Juara, 2020)
The purpose of the research is to analyze about suffixes use in English textbook for senior high school on tenth grade. Morphology is the study of morphemes which are the smallest significant units of grammar. There are two kinds of morphology, they are derivational and inflectional. Affixes such as suffixes, infixes, prefixes, ablaut and reduplication are kinds of derivational morphology, meanwhile plural, possessive, past time, progressive, comparative and superlative are kinds of inflectional morphology. Morphology relates to grammar. Grammar is one apsect in studying English. The apsects in grammar sometimes confuse not only the students but also the teachers. Data was taken from English textbooks used by senior high school, English Zone and English book. The participants of this research were the grade tenth students in senior high school. To do the research they were asked to Based on the analyses, it is found that the aspects of grammar focus are revealed in every word. The results of this research are